Hepatitis C among blood donors: cascade of care and predictors of loss to follow-up - Soraia Mafra Machado; Cesar de Almeida Neto; João Renato Rebello Pinho; Fernanda de Mello Malta; Ligia Capuani; Aléia Faustina Campos; Fatima Regina Marques Abreu; Ana Catharina de Seixas Santos Nastri; Rúbia Anita Ferraz Santana; Ester Cerdeira Sabino; Maria Cássia Mendes-Correa
ABSTRACT OBJECTIVE To investigate the HCV cascade of care and to identify the factors associated with loss or absence to follow-up of patients identified as infected with hepatitis C through blood donation. METHODS Blood donors from 1994 to 2012, identified with positive anti- HCV by enzyme immunoassay and immunoblot tests were invited to participate in the study, through letters or phone calls. Patients who agreed to participate were interviewed and their blood samples were collected for further testing. The following variables were investigated: demographic data, data on comorbidities and history concerning monitoring of hepatitis C. Multiple regression analysis by Poisson regression model was used to investigate the factors associated with non-referral for consultation or loss of follow-up. RESULTS Of the 2,952 HCV-infected blood donors, 22.8% agreed to participate: 394 (58.2%) male, median age 48 years old and 364 (53.8%) Caucasian. Of the 676 participants, 39.7% did not receive proper follow-up or treatment after diagnosis: 45 patients referred not to be aware they were infected, 61 did not seek medical attention and 163 started a follow-up program, but were non-adherent. The main reasons for inadequate follow-up were not understanding the need for medical care (71%) and health care access difficulties (14%). The variables showing a significant association with inadequate follow-up after multiple regression analysis were male gender (PR = 1.40; 95%CI 1.15-1.71), age under or equal to 50 years (PR = 1.36; 95%CI 1.12-1.65) and non-Caucasians (PR = 1.53; 95%CI 1.27-1.84). CONCLUSIONS About 40.0% of patients did not receive appropriate follow-up. These data reinforce the need to establish strong links between primary care and reference centers and the need to improve access to specialists and treatments.